Effect of Rebound Hammer Test Point Location on the Variability and Accuracy of Concrete Compressive Strength Estimation - Y Djoko Setiyarto; Muhammad Pramudita Mustopa (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
Concrete compressive strength is a fundamental parameter for evaluating the performance of concrete structures. Although destructive testing using a Compression Testing Machine (CTM) is considered the most accurate method, its limited applicability to existing structures has led to the use of non-destructive methods, such as the rebound hammer test. However, rebound hammer results often deviate from CTM measurements, raising concerns regarding their reliability. This study examines the impact of rebound hammer test point location on the variability and accuracy of estimated concrete compressive strength, and assesses its agreement with destructive test results. A quantitative laboratory experimental program was conducted using concrete with a target strength of 15 MPa. Five cylindrical and five cubic specimens were tested at 28 days. Rebound hammer tests were performed on top, bottom, and side surfaces in accordance with ASTM C805, followed by destructive compressive strength testing using CTM based on ASTM C39. The results show that test point location systematically influences rebound hammer outcomes. Bottom test points produce the highest estimated strengths and the largest deviations from CTM results, whereas top test points yield the closest agreement with actual compressive strength. The findings confirm that rebound hammer accuracy is position-dependent and should be explicitly considered in concrete strength evaluation.